Preparation of laser markable polyamide compounds. Issue 1 (January 2021) - Li, W H
Abstract: Laser marking technique has been increasingly used in electrical and electronic industry in the recent decades for scanning and control purpose. Laser marking is superior to the traditional labelling techniques in terms of speed, flexibility and duration. The mechanism of laser marking is either blackening by carbonization or brightening by microbubbles, upon the effect of laser on the base. Normally laser marking additives were introduced in order to achieve the controllable marking effect. In this paper, a light-on-dark laser markable polyamide compound was studied with the leveraged properties of mechanical, physical and laser marking effect.